2006
DOI: 10.1007/s00421-006-0323-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered tension cost in (TG(mREN-2)27) rats overexpressing the mouse renin gene

Abstract: The present study aimed to characterize cardiac hypertrophy induced by activation of the renin-angiotensin system in terms of functional alterations on the level of the contractile proteins, employing transgenic rats harboring the mouse renin gene (TGR(mREN2)27). Ca2+-dependent tension and myosin ATPase activity were measured in skinned fiber preparations obtained from TGR(mREN2)27 and from age-matched Sprague-Dawley rats (SPDR). Western blots for troponin I (TnI) and troponin T (TnT) were performed and the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…That is, we found reduced force-dependent ATP consumption rate (tension-cost), reduced force redevelopment rate (K tr ), and prolongation of myofilament relaxation time (Time lin ). We and others have previously reported similar findings in rat models of cardiac disease ( Daniels et al, 2007 ; Zobel et al, 2007 ; Patel et al, 2017 ). However, as discussed above, a significant shift in myosin isoform expression is seen in this species during cardiac stress ( Daniels et al, 2007 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…That is, we found reduced force-dependent ATP consumption rate (tension-cost), reduced force redevelopment rate (K tr ), and prolongation of myofilament relaxation time (Time lin ). We and others have previously reported similar findings in rat models of cardiac disease ( Daniels et al, 2007 ; Zobel et al, 2007 ; Patel et al, 2017 ). However, as discussed above, a significant shift in myosin isoform expression is seen in this species during cardiac stress ( Daniels et al, 2007 ).…”
Section: Discussionsupporting
confidence: 87%
“…α-MHC is the faster molecular motor, displaying three- to fivefold faster actin-activated ATPase activity, time to peak systole, shortening velocity, and cross-bridge cycling kinetics compared with β-MHC ( van der Velden et al, 1998 ; Rundell et al, 2005 ; Locher et al, 2009 ; Chen et al, 2010 ; Locher et al, 2011 ; de Tombe and ter Keurs, 2012 ). Most of the studies documenting depressed cross-bridge cycling kinetics in the failing heart have been done either in rats or mice ( Rundell et al, 2004 ; Daniels et al, 2007 ; Zobel et al, 2007 ; Patel et al, 2017 ). Rats and mice almost exclusively express the alpha isoform of myosin (α-MHC) in their ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…The Ren2 model develops cardiac hypertrophy that leads to adaptive alterations in the level of the contractile filaments (56). The increase in ␤-myosin heavy chain expression (56) may partially be responsible for the observed LV diastolic dysfunction in the Ren2 heart.…”
Section: Effects Of Nebivolol On In Vivo Cardiac Function In Ren2 Amentioning
confidence: 99%
“…The decrease in cross-bridge kinetics could be another representation of the development of cardiac pathology. Although a lower tension-cost indicates more efficient ATP utilization (Rundell et al, 2004;Rundell et al, 2005), decreased tension-cost has also been found in many pathological models (Rundell et al, 2004;Zobel et al, 2007).…”
Section: Weeksmentioning
confidence: 99%